What Industry Wants: An Empirical Analysis of Health Informatics Job Postings - McLane, Tara M.; Hoyt, Robert; Hodge, Chad; Weinfurter, Elizabeth; Reardon, Erin E.; Monsen, Karen A. (Applied Clinical Informatics, 2021)
Objectives To describe the education, experience, skills, and knowledge required for health informatics jobs in the United States.Methods Health informatics job postings (n = 206) from Indeed.com on April 14, 2020 were analyzed in an empirical analysis, with the abstraction of attributes relating to requirements for average years and types of experience, minimum and desired education, licensure, certification, and informatics skills.Results A large percentage (76.2%) of posts were for clinical informaticians, with 62.1% of posts requiring a minimum of a bachelor's education. Registered nurse (RN) licensure was required for 40.8% of posts, and only 7.3% required formal education in health informatics. The average experience overall was 1.6 years (standard deviation = 2.2), with bachelor's and master's education levels increasing mean experience to 3.5 and 5.8 years, respectively. Electronic health record support, training, and other clinical systems were the most sought-after skills.Conclusion This cross-sectional study revealed the importance of a clinical background as an entree into health informatics positions, with RN licensure and clinical experience as common requirements. The finding that informatics-specific graduate education was rarely required may indicate that there is a lack of alignment between academia and industry, with practical experience preferred over specific curricular components. Clarity and shared understanding of terms across academia and industry are needed for defining and advancing the preparation for and practice of health informatics.
Keywords: informatics; medical informatics; job description; employment; health workforce; workforce; training and education requirements; clinical informatics; nurse; informatics specialists